Analisis Usaha Pembenihan Ikan Mas Mina Jogja Istimewa (Najawa) dengan Sistem Pemijahan Alami - Wijianto; Effendi, Irzal (JAGO TOLIS : Jurnal Agrokompleks Tolis, 2025)
Najawa carp is one of the carp developed at BPTPB Cangkringan and has economic value. Market demand for Javanese carp is at the larval stage. This is the reason why fish spawning activities are routinely carried out to obtain larvae that are ready to be sold. Business analysis needs to be done to evaluate the feasibility of the najawa carp seeding business. The purpose of this study was to evaluate the feasibility of the najawa carp seeding business with a natural spawning system. The data taken were primary data, namely direct observation and secondary data obtained from interviews. Data analysis included investment costs, fixed costs, variable costs, total costs, R/C ratio, break event point, payback period, and cost of production. The results of the analysis showed a payback period value of 2.08, an R/C ratio value of 1.22, a BEP unit of 2,053,120.61, and a BEP price of 151,564,296.4. The najawa carp seeding business with a natural spawning system is feasible to be developed.